Cannabis and pathologies in dogs and cats: first survey of phytocannabinoid use in veterinary medicine in Argentina - Banach, Diana (2023)
Background: In animals, the endocannabinoid system regulates multiple physiological functions. Like humans, animals respond to preparations containing phytocannabinoids for treating several conditions. In Argentina, laws 27350 and 27669 have expanded the possibility of studying beneficial and adverse effects. Materials and methods: We conducted a web-based survey of Argentinian Cannabis Veterinarians to make a situational diagnosis on the number of veterinary medicine professionals currently developing treatments with cannabinoids focusing on dogs and cats. Results: Among the species treated, 77% corresponded to dogs, while 21% were cats. Pain, seizures, and behavior disorders are the most prevalent conditions in dogs. Seven conditions and combinations were treated in cats. Full-spectrum cannabis extract derived from three different chemotypes was administered alone or with standard medication. Response to cannabis treatment was characterized based on improvement categorized according to clinical assessment. Both dogs and cats showed different improvement grades in clinical signs. Conclusion: This analysis provides promising results regarding the medicinal use of cannabis in dogs and cats. Based on this analysis, we propose to expand the training of professionals, obtain quality preparations, and initiate controlled trials to reinforce knowledge of the use of cannabinoids in veterinary medicine.